The strain fields present during the bending of ultra-high strength steels. (2017) - Hazra, Sumit; Efthymiadis, Panos; Proprentner, Daniela; Shollock, Barbara; Dashwood, Richard
Abstract: Ultra high strength steels (UHSS) have an ultimate tensile strength of greater than 1GPa. Typically, their ambient temperature elongation is less than 10% and as a result, they are rarely used in stamping applications. However, the continuous demand for the weight reduction of structures built for the transport sector means that such materials are attractive because they can be used for parts with thinner cross-sections while maintaining required in-service performance. One way to overcome the ambient temperature ductility of these materials is to roll-form them, particularly with emerging flexible roll forming technology. Using numerically-controlled actuators, the rolls on each stand are designed with sufficient degrees of freedom to form parts that curve, vary in depth and width along their lengths. This makes flexibly roll-formed parts attractive to the transport, particularly the automotive, sector. Roll forming deforms a material through incremental, localised bending, which is known to suppress the necking response, resulting in deformations that are higher than in stretch deformation. Recent work, such as Le Maoût, Thuillier & Manach, Eng. Frac. Mech., Vol. 76, p.1202 (2009), focussed on the development of ductile fracture models to explain failure but their validation was limited to load displacement and surface strain data. This work aims to characterise the strain field during bending more comprehensively. Using the digital image correlation technique, the macroscopic strain distribution in UHSS in the thickness of the sheet and the strain partitioning in its microstructure is measured during bending. The data provides a detailed explanation of the strain distribution during bending.